Pregnancy and broken cavernous hemangioma of the liver - Molina V., Lucas (2015)
A woman of 26 with 8 1/2 months had symptoms of acute abdominal pain and shock pregnancy is described; and simulating a uterine rupture. During surgery, a cavernous hemangioma of the liver was found; conservative treatment (hemostasis and drainage) succeeded. The importance of high estrogen levels on the growth of these tumors is highlighted.